Prevalence of Underweight, Stunting and Thinness Among Adolescent Girls in Kavre District - Mansur, Dil Islam; Haque, Mohammad Khurshidul; Sharma, Kalpana; Mehta, Dilip Kumar; Shakya, Rojina (Journal of Nepal Paediatric Society, 2016)
Introduction: Poor nutritional status during adolescence is an important determinant of health outcome. The adolescents have different needs and have diverse problems. Nutritional assessments among adolescents are important as they are the future parents and constitute a potentially susceptible group. The present study is an attempt to evaluate the prevalence of underweight, stunting and thinness including overweight among adolescent girls from rural community. Material and Methods: A cross-sectional study was conducted among school going adolescent girls, 9-16 years studying in various schools in rural area of Kavre district, Nepal during 15thMarch to 15th September 2014. The weight and height were recorded from each participant in kilogram and centimetre respectively, and nutritional status of the adolescent girls was assessed through the Z-scores of underweight (weight for age), stunting (height for age) and thinness (BMI for age) according to WHO criteria. Data was entered and analyzed by using SPSS 19.0. Results: The overall prevalence of underweight, stunting and thinness was 31.98%, 21.08% and 14.94% respectively. It was concluded that highest (49.5%) prevalence of underweight was among 11 years of adolescent girls and the lowest (20.7%) was found in the age group of 13 years. Stunting was highest in age group of 9 years (37.34%) and the lowest prevalence of stunting was 10.7% in the age group of 14 years. The highest prevalence (24.2%) of thinness was found in 9 years and lowest prevalence (11.0%) was found in 10 years adolescent girls. Conclusion: It is concluded that there is a high prevalence of under nutrition among studied adolescent girls in the rural areas of Kavre district. Health education and nutrition interventions are needed on priority basis. J Nepal Paediatr Soc 2015;35(2):129-135